Effects of seaweed-based biostimulants on the morphophysiological profile of lettuce (Lactuca sativa L.) - Seily Cuchca Ramos; Ligia García; José I. Barboza; Danilo E. Bustamante; Martha S. Calderon (Cogent Food & Agriculture)
The use of biostimulants is considered an environmentally friendly agricultural practice that enhances soil minerals availability as well as soil structure and quality. In this study, marine macroalgae were collected from central Peru (Macrocystis pyrifera and Ulva sp.) to elaborate biostimulants via a combination of extraction methods that included ultrasonic‑assisted extraction (UAE) and ultrasonic‑assisted enzyme extraction (UAEE). This research aimed to evaluate the effects of these seaweed‑based biostimulants on the morphophysiological profile of lettuce (Lactuca sativa L.). For this purpose, a complete randomized design (CRD) with eight treatments and five observations was established. For this design, four biostimulants of green and brown macroalgae produced via four different extraction methods (formulas protected for a patent process) and three commercial biostimulants were employed. A total of 18 variables were evaluated to determine the morphology (10), physiology (3), and biochemical composition (5) of the lettuce plants. Our results revealed that the biostimulant composed of green macroalgae obtained using UAEE at a dose of 4 mL/L had positive effects on morphological and physiological parameters, representing an improvement on what was observed in the samples in the control treatment. These results confirmed the potential of these seaweed‑based biostimulants from the Peruvian coast for organic agriculture and sustainable crop development.